Application of Local Wisdom-Based Discovery Learning Model to Improve Students' Learning Motivation - Nilna Najwa Kamila; Beni Setiawan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
In the field of education, an individual's success in achieving learning competencies is influenced not only by intellectual factors but also by equally significant non-intellectual factors, such as self-motivation. The purpose of this study is to demonstrate that using a discovery learning model grounded in local wisdom improves students' learning motivation. This research measures the following characteristics of learning motivation: Attention, Relevance, Confidence, and Satisfaction (ARCS). Thirty-five kids from State Junior High School 1, Jetis Ponorogo's class VIII-B, served as the research subjects. As part of a quantitative research design, the study employed a pre-experimental type with a one-group pretest-posttest. Motivation levels were measured using a questionnaire, and learning implementation was observed using an observation sheet. N-Gain analysis and the Wilcoxon test were used to analyze the data. learning motivation. Analysis of learning implementation data using Likert scale analysis. Learning motivation had improved, as indicated by an N-Gain score of 0.67, which is categorized as a medium gain. Furthermore, the Wilcoxon test yielded an asymptotic significance value (2-tailed) of <0.001, showing a significant difference between students' learning motivation before and after the local wisdom-based discovery learning was implemented. The percentage of learning implementation from the three meetings reached 92%, categorised as excellent. Based on the results of the research, using a local wisdom-based discovery learning successfully raises students' motivation to learn. Among the motivation aspects, 'Confidence' showed the greatest improvement, whereas 'Satisfaction' recorded the lowest. Consequently, the application of this model should be integrated with reflection and meaning reinforcement to further improve students' learning satisfaction.